The Effectiveness of Problem-Based Learning Assisted by Canva and Learning Interest on Critical Thinking Skills in 4th Grade - Nadia Rahmantika; St. Y Slamet; Kartika Chrysti Suryandari3; Fida Rahmantika Hadi (Journal of Science and Education (JSE), 2026)
Every human being is required to have the ability to be able to adapt to the times, one of which is the ability to think critically. However, students' critical thinking skills are still not good or lacking. The purpose of this study was to determine the effect of the Problem Based Learning learning model assisted by Canva on critical thinking skills. To determine the effect of students' interest in learning on critical thinking skills. To determine the interaction of the learning model and ask students to learn critical thinking skills. The method used is quantitative. The subjects in this study were fourth grade students. Data collection techniques with tests and questionnaires. The sample in this study amounted to 93 students with random sampling. Data analysis techniques to test the hypothesis using two-way Anova. The results showed that there was a significant effect of using the Problem Based Learning learning model assisted by Canva on critical thinking skills, there was a significant effect of learning interest on critical thinking skills, there was no interaction between learning models and learning interest on critical thinking skills.